Exposure Assessment and Health Risk of Polybrominated Diphenyl Ether (PBDE) Flame Retardants in Indoor Environments of Children’s Facilities in Korea - Ho-Hyun Kim; Ji-Yeon Yang; Yun-Suk Jang; Yong-Jin Lee; Chung-Soo Lee; Dong-Chun Shin; Young-Wook Lim (Asian Journal of Atmospheric Environment, 2011)
This study assessed the health risks of childhood exposure to PBDEs via different possible pathways in children’s facilities and indoor playgrounds. When PBDE contamination was measured, it was determined through multiple routes, including inhalation of indoor dust, dermal contact with product surfaces and children’s hands, and incidental dust ingestion. Samples were collected from various children’s facilities (playrooms, daycare centers, kindergartens, and indoor playgrounds) during summer (Jul-Sep, 2007) and winter (Jan-Feb, 2008). The hazard index (HI) was estimated for non-carcinogens, and PBDEs, such as TeBDE, PeBDE, HxBDE, and DeBDE, were examined. The sensitivity to the compounds did not exceed 1.0 (HI) for any of the subjects in any facility. However, current data about toxicity does not reflect effects that were fully sensitive in children, so there is uncertainty in the dose-response data. The contribution rates of PBDEs were 71.4 to 96.1% and 3.7 to 28.2% for intake and inhalation exposure, respectively, indicating that intake of floor dust and inhalation are the primary routes.